Inuit settlement in the Clyde area during “contact-exploration” times (ca. 1820-1895) - Wenzel, George (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2008)
AbstractBoas, in his classic The Central Eskimo (1888), strongly implied that at the time of his most northerly journey the Baffin Island coast between northern Home Bay and Eclipse Sound, what is today the Clyde River area, was at most only lightly utilised by Inuit. Ethnohistorical inquiry about Inuit settlement in the area prior to a European presence was frustrated by a lack of temporal referencing for much of the information received from Clyde elders. However, more success was achieved by using temporally situated literature references as cues for informants. This paper relates Clyde Inuit recollections to three reports about 19th century Inuit in the region. The earliest of these (1820) occurred almost at the site of modern Clyde River, while the other two reports are both within a decade of Boas’s journey. These accounts, coupled with Mathiassen’s (1928) information from Inuit at Pond Inlet about their birthplaces and travels, suggest that the Clyde area, while perhaps not intensively occupied, was far from unknown to Inuit.